MILLENNIAL WOMEN'S CHALLENGES TOWARDS INDONESIA'S BLUE ECONOMIC WELFARE POLICY (Lex localis - Journal of Local Self-Government, 2025)
It is a Participatory Action Research with a qualitative approach of Interactive Qualitative Analysis for the Indonesian Millennial Women who were perceived encountered by the Indonesia Blue Economy Outlooks. It was prioritizing the women millennials as mandated by the IORA. This approach emphasizes an equal relationship between researchers and participants and prioritizes actions that benefit the community.The results were then proceeded by a single FGI (Focus Group Interview), for triangulation purposes, with 54 individuals, i.e.: 28 millennial women ex-FGDs who were accompanied by 26 husbands, all of whom were identified as sufficiently proficient for the Indonesia Blue Economy Roadmap. The pivot or the basic counter-beliefs are for the ‘Needs of Women Renaissance Movements’ as the central beliefs for the blue economy successes, with every woman exploring the ‘Motherly Spirit of Honesty’ and the ‘Motherly Spirit of Fairness’ sooner than those would certainly cultivate the secondary outcomes for the ‘Equality Economic Distributions’ and the ‘Advance of the Grassroots Communities Welfares’. Finally, it also found that the impactful primary outcomes are for the ‘Indonesian Blue Economy Wholesome Progresses’ and for the ‘Sustainable Indo-Pacific Economy.’ From this study, there was also an exclusive response about the belief for ‘the Better Trickle-Down Effects for the Grassroots’ and the ‘Indonesia Nickel-Ore Downstream Dilemma’, since further for the ‘Working Hand in Hand Amongst Female and Male Millennials’ with the ‘Emancipatory Leadership’ would then be capably inducing the higher impactful for again the ‘Advance of the Grassroots Economic Welfares’.